The Editor's Note: From what it's not to what it is. (October 2019) - Heller, Rafael
Since the Every Student Succeeds Act (ESSA) was passed in December 2015, policy debates about the law have focused not so much on what it does, but on the ways in which it undoes No Child Left Behind. All the same, ESSA has begun to result in real changes on the ground, in many parts of the country. And now that states have completed the writing of their ESSA plans and have moved on to implementing them, attention has begun to shift from what ESSA is not to what is, in fact, going on under the new law .